2021
DOI: 10.1177/08862605211028011
|View full text |Cite
|
Sign up to set email alerts
|

Is This WhatsApp Conversation Aggressive? Adolescents’ Perception of Cyber Dating Aggression

Abstract: This study investigated adolescents’ understanding of cyber dating aggression in terms of frequency and aggressiveness: how prevalent they perceived cyber dating aggression among adolescents and how aggressive they perceived such behaviors to be. To do so, different WhatsApp scenarios were presented to adolescents, controlling for the typology of cyber dating aggression (verbal/emotional, controlling, or sexual) and its publicity (public or private cyber dating aggression). The moderating effect of gender and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…This result could be explained based on the previous evidence available. High normalisation of cyber dating violence, specifically online control, among young people has been shown (Rueda et al, 2015; Sánchez‐Jiménez et al, 2021), leading adolescents to carry out these types of behavior without realising, in many cases, that they are engaging in violent behavior. In this respect, these results highlight the need to develop cyber dating violence awareness campaigns for the prevention of dating violence (Muñoz‐Fernández & Sánchez‐Jiménez, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This result could be explained based on the previous evidence available. High normalisation of cyber dating violence, specifically online control, among young people has been shown (Rueda et al, 2015; Sánchez‐Jiménez et al, 2021), leading adolescents to carry out these types of behavior without realising, in many cases, that they are engaging in violent behavior. In this respect, these results highlight the need to develop cyber dating violence awareness campaigns for the prevention of dating violence (Muñoz‐Fernández & Sánchez‐Jiménez, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that: (H1) online jealousy would be a strong predictor of online control among boys and girls (Branson & March, 2021; Deans & Bhogal, 2019); (H2) moral disengagement would be a strong moderator between online jealousy and online control among boys and girls. Based on previous findings regarding the moderating role of moral disengagement in the association between sexism and dating aggression (Sánchez-Jiménez & Muñoz-Fernández, 2021) and the influence of this cognitive component on the perception of online control (Sánchez-Jiménez et al, 2021), we expected higher levels of moral disengagement to strengthen the relationship between online jealousy and online control. (H3) socio-emotional competence would moderate the association between online jealousy and online control.…”
Section: The Present Studymentioning
confidence: 98%
“…Concerning moral disengagement, in contrast, studies have consistently found higher levels among boys than among girls (Rubio-Garay et al, 2015, 2019). However, these gender differences do not seem to influence the predictive value of moral disengagement for dating aggression since this association is significant for both boys and girls (Sánchez-Jiménez et al, 2021).…”
Section: Gender Differences In Online Control and Associated Variablesmentioning
confidence: 99%
See 2 more Smart Citations